Czech version of OPQOL-35 questionnaire: the evaluation of the psychometric properties - Mares, Jiri; Cigler, Hynek; Vachkova, Eva (Health and quality of life outcomes, 2016)
BACKGROUND: Both prognoses and real demographic trends in developed countries point to the increasing proportion in the population of people above 65 years of age. One of important themes of care for seniors is the assessment of their quality of life. To evaluate the quality of life of seniors three types of tools can be used: general generic tools; generic tools used for the age group of elderly persons; specific tools to detect the quality of life of the elderly who are affected by specific diseases. METHODS: The second type of tool is represented by the OPQOL - 35 questionnaire (Older People's Quality of Life Questionnaire), which was developed in the UK. It has 35 items and deals with 8 domains of quality of life. With the consent of the author the questionnaire was translated into Czech and verified in a group of 478 seniors aged 60 and above (40 % males, 60 % females). Unlike the British version, the Czech version has seven factors: 1 Role of belief, religion and culture; 2 Health; independence, active life; 3 Financial situation; 4 Family and safe environment; 5 Loneliness; 6 Satisfaction with life; 7 Positive approach to life. RESULTS: The Czech version has a very good reliability (Cronbach's alpha ranges from .726 to .905). It also has satisfactory validity. The results show that with increasing age and number of health problems the satisfaction of the elderly is declining in all seven domains. Conversely, the degree of autonomy in the way of living is positively associated with the satisfaction of seniors. Old people who live alone at home, are self-sufficient and do not need the help of others, are more satisfied with their quality of life than other seniors (i.e..those who are living with their children, in sheltered accommodation or in homes for the elderly). Single, married seniors and seniors with a partner are happier than the widowed ones. CONCLUSIONS: The questionnaire gives good guidance for assessing the current state of the quality of life of seniors, changes in quality over time and for targeted interventions as well.
Keywords: sociální opora; Czech Republic; Česká republika; osamocení; Quality of Life; Reproducibility of Results; Reliability; Personal Satisfaction; průzkumy a dotazníky; Surveys and Questionnaires; Quality of life; OPQOL-35 questionnaire; Humans; stárnutí; Factor structure; osobní uspokojení; Seniors; Female; Loneliness; Aged; reprodukovatelnost výsledků; Aging; zdravotní stav; Male; kvalita života; senioři; Social Support; etnicita; Health Status; ženské pohlaví; psychometrie; senioři nad 80 let; Aged, 80 and over; Ethnicity; Validity; Assessment; Psychometrics; lidé; mužské pohlaví